2019
DOI: 10.1111/pce.13554
|View full text |Cite
|
Sign up to set email alerts
|

Rice sulfoquinovosyltransferase SQD2.1 mediates flavonoid glycosylation and enhances tolerance to osmotic stress

Abstract: Sulfoquinovosyltransferase 2 (SQD2) catalyses the final step in the sulfoquinovosyldiacylglycerol (SQDG) biosynthetic pathway. It is involved in the phosphate starvation response. Here, we show that rice SQD2.1 has dual activities catalysing SQDG synthesis and flavonoid glycosylation. SQD2.1 null mutants (sqd2.1) in rice had decreased levels of glycosidic flavonoids, particularly apigenin 7‐O‐glucoside (A7G), whereas these metabolites were increased in rice plants overexpressing SQD2.1. The sqd2.1 mutants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…A number of major QTLs regulating grain size have been identified and found to be involved in the ubiquitin-proteasome pathway, G-protein signaling, mitogenactivated protein kinase signaling, phytohormones signaling, and regulation of transcriptional factors 1 . Flavonoids accumulate in response to abiotic stress and protect plants by scavenging ROS and reducing oxidative damage [21][22][23][24]47 . However, our knowledge of the mechanism underlying the synergistic regulation of grain yield and abiotic stress tolerance remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of major QTLs regulating grain size have been identified and found to be involved in the ubiquitin-proteasome pathway, G-protein signaling, mitogenactivated protein kinase signaling, phytohormones signaling, and regulation of transcriptional factors 1 . Flavonoids accumulate in response to abiotic stress and protect plants by scavenging ROS and reducing oxidative damage [21][22][23][24]47 . However, our knowledge of the mechanism underlying the synergistic regulation of grain yield and abiotic stress tolerance remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids including anthocyanins have been extensively studied for their roles in protecting plant against abiotic stress 21,22,24 . A recent study revealed that flavonoid glycosides such as apigenin glucoside derivatives, particularly apigenin-7-O-glucoside and chrysoeriol glucoside derivatives accumulate under abiotic stress and act as ROS scavengers to reduce oxidative damage in rice 47 . Consistent with this, the relative levels of these flavonoid glycosides and anthocyanins were clearly reduced in NIL-GSA1 CG14 , which is more sensitive to abiotic stress than NIL-GSA1 WYJ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids function as antioxidants that reduce oxidative damage caused by reactive oxygen species (ROS) accumulation, which is induced by abiotic stresses such as soil salinity, drought, and extreme temperatures (Nakabayashi and Saito, 2015; Jiang et al, 2016; Figure 2). Treatment with flavonoids such as naringenin, apigenin 7‐ O ‐glucoside, and rutin, decreases oxidative damage and enhances tolerance to osmotic stresses such as salt and drought stress in rice, bean ( Phaseolus vulgari s) and tobacco (Zhan et al, 2019; Chen et al, 2019c; Yildiztugay et al, 2020). Overexpression of flavonoid structural genes such as CHS and DFR increases the levels of flavonol glycosides and anthocyanins, reduces ROS accumulation, and enhances tolerance to salt stress in rice (Cui et al, 2014), Brassica napus L. ‘Hanla’ (Kim et al, 2017), and tobacco (Chen et al, 2019c).…”
Section: Biofunctions Of Phenylpropanoid Metabolitesmentioning
confidence: 99%
“…ROS was detected using nitrotetrazolium blue chloride (NBT; Sangon) based on a method described by Zhan et al, (2019). To visualize ROS, leaves were sampled and stained with 6 mM NBT in phosphate buffer (50 mM NaH 2 PO 4 , 50 mM Na 2 HPO 4 , 150 mM NaCl, and 10 mM KCl, pH 7.5) for 1 h after chlorophyll was removed with 70% (v/v) ethanol.…”
Section: Measurement Of Ros and H 2 O 2 Contentsmentioning
confidence: 99%